Efficiency of Herb Crude Extracts to Inhibit the Growth of Penicillium citrinum Aspergillus flavus var. flavus and Aspergillus tamarii Isolated from the Rubber Sheet - ชูวัฒน์วรกูล, ธัญญ์วาริน; ทวีพานิชย์, สมจินตนา; สุวรรณกูฏ, พิชญาภรณ์; ลําลอง, สายสมร (KKU Science Journal, 2017)
This research studied the efficiency of crude extracts from herbs to inhibit the growth of Penicillium citrinum, Aspergillus flavus var. flavus and Aspergillus tamarii. These fungi were isolated from rubber sheet. Seven herbs including garlic, galangal, betel, clove, cinnamon, ringworm bush and lemon grass were extracted by hexane, ethyl acetate and methanol. The crude extracts were tested the efficiency for inhibiting fungal growth by paper disc diffusion method. It was found that the most effective crude herb extract to inhibit the growth of P. citrinum and A. flavus var. flavus at concentration 100,000 ppm was cinnamon which was extracted with ethyl acetate. The average diameters of the inhibition were of 41.50 and 25.93 mm, respectively. While the crude extract of galangal extraction with ethyl acetate was the most effective for inhibiting the growth of A. tamarii with the average diameter of the inhibition of 25.83 mm. The minimum inhibitory concentration (MIC) of cinnamon extraction with hexane and ethyl acetate, galangal extraction with methanol was effective in inhibiting the growth of P. citrinum by the MIC were 25,000, 12,500 and 25,000 ppm, respectively. In addition, cinnamon extraction with hexane and ethyl acetate, galangal extraction with methanol was effective in inhibiting the growth of A. flavus var. flavus by the MIC was 50,000, 25,000 and 50,000 ppm, respectively. Galangal extract with hexane, ethyl acetate and methanol was effective in inhibiting the growth of A. tamarii by the MIC was 781.25, 390.63 and 3,125 ppm, respectively.